Hybrid artificial intelligent systems : 13th International Conference, HAIS 2018, Oviedo, Spain, June 20-22, 2018, Proceedings /: 13th International Conference, HAIS 2018, Oviedo, Spain, June 20-22, 2018, Proceedings. (2018) - Unknown
No abstract available